2008
DOI: 10.1016/j.bbr.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Gabrb3 gene deficient mice exhibit impaired social and exploratory behaviors, deficits in non-selective attention and hypoplasia of cerebellar vermal lobules: A potential model of autism spectrum disorder

Abstract: The observed behavioral deficits, especially regarding social behaviors, strengthens the face validity of the gabrb3 gene deficient mouse as being a model of autism spectrum disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(165 citation statements)
references
References 76 publications
8
156
1
Order By: Relevance
“…Holding associations to a standard of 100% replication would be similar to dismissing the role of a particular mutation after not seeing it in a small case series. Additional support for the common variant approach comes from data indicating that mice with mutations in genes for which association is well established (for example, reelin and Gabrb3) show ASDlike abnormalities 73,74 . Not only should rare and common variant approaches be pursued in parallel, but an integration of the results from both methods will also be necessary.…”
Section: Association Studiesmentioning
confidence: 99%
“…Holding associations to a standard of 100% replication would be similar to dismissing the role of a particular mutation after not seeing it in a small case series. Additional support for the common variant approach comes from data indicating that mice with mutations in genes for which association is well established (for example, reelin and Gabrb3) show ASDlike abnormalities 73,74 . Not only should rare and common variant approaches be pursued in parallel, but an integration of the results from both methods will also be necessary.…”
Section: Association Studiesmentioning
confidence: 99%
“…Social behavior assays have been conducted with many of the mouse models in which imaging studies were conducted. Employing our 3-chambered social approach task, a simple yes-or-no assay for sociability [13], absence of sociability was reported in mice with mutations in genes including Shank3 [15,16], Cntnap2 [17], Pten [18], Tsc1 [19], En2 [20], Gabrb3 [21], Ube3a triplication [22], and oxytocin receptor knockouts [23]. Normal 3-chambered social approach appeared in mice with mutations in genes including oxytocin [24], Shank1 [25], Nlgn2 [26], Ephrin-A [27] and 16p11.2 deletion [28] Variable findings on social approach across laboratories and in mouse lines generated on different genetic backgrounds have been reported for mutations including Fmr1 [29,30], Nlgn3 [31][32][33][34], and Nlgn4 [35,36].…”
Section: Discoveries Of Autism-relevant Behaviors In Mouse Modelsmentioning
confidence: 99%
“…Interestingly, one study showed that the GABRB3 gene was monoallelically expressed in autistic brain samples, whereas it was biallelically expressed in control samples [160], implying altered GABA signaling in ASD. Inactivation of GABRB3, conventionally or conditionally, in mice results in significant impairments in development, and social behaviors, and also causes stereotypical behavior [161][162][163][164].…”
Section: The Gamma-aminobutyric Acid Receptor Subunit Beta-3 (Gabrb3)mentioning
confidence: 99%